Effect of steel, cooper, and lead projectile impact on the damage process of brittle materials - Shah, Qasim Hussain (s.n, 2012)
In this research, Barre granites are subjected to localized impacts of spherical projectiles with density variation. Three kinds of projectiles have been used, namely chrome steel, copper 102 and pure lead. The amount of damage is studied on both brittle target as well as ductile projectile. The result shows significance of intact time for free edge impact, while projectile's higher stiffness causes more damage on high constraint surface impact.